Promising prospects of nanopore sequencing for algal hologenomics and structural variation discovery - Sauvage, Thomas (BMC Genomics, 2019)
BACKGROUND: The MinION Access Program (MAP, 2014–2016) allowed selected users to test the prospects of long nanopore reads for diverse organisms and applications through the rapid development of improving chemistries. In 2014, faced with a fragmented Illumina assembly for the chloroplast genome of the green algal holobiont Caulerpa ashmeadii, we applied to the MAP to test the prospects of nanopore reads to investigate such intricacies, as well as further explore the hologenome of this species with native and hybrid approaches. RESULTS: The chloroplast genome could only be resolved as a circular molecule in nanopore assemblies, which also revealed structural variants (i.e. chloroplast polymorphism or heteroplasmy). Signal and Illumina polishing of nanopore-assembled organelle genomes (chloroplast and mitochondrion) reflected the importance of coverage on final quality and current limitations. In hybrid assembly, our modest nanopore data sets showed encouraging results to improve assembly length, contiguity, repeat content, and binning of the larger nuclear and bacterial genomes. Profiling of the holobiont with nanopore or Illumina data unveiled a dominant Rhodospirillaceae (Alphaproteobacteria) species among six putative endosymbionts. While very fragmented, the cumulative hybrid assembly length of C. ashmeadii’s nuclear genome reached 24.4 Mbp, including 2.1 Mbp in repeat, ranging closely with GenomeScope’s estimate (> 26.3 Mbp, including 4.8 Mbp in repeat). CONCLUSION: Our findings relying on a very modest number of nanopore R9 reads as compared to current output with newer chemistries demonstrate the promising prospects of the technology for the assembly and profiling of an algal hologenome and resolution of structural variation. The discovery of polymorphic ‘chlorotypes’ in C. ashmeadii, most likely mediated by homing endonucleases and/or retrohoming by reverse transcriptases, represents the first report of chloroplast heteroplasmy in the siphonous green algae. Improving contiguity of C. ashmeadii’s nuclear and bacterial genomes will require deeper nanopore sequencing to greatly increase the coverage of these larger genomic compartments.